Investigating associations between cognitive empathy, affective empathy and anxiety in adolescents with autism spectrum disorder. - Sönmez, Dilruba; Jordan, Timothy R. (International Journal of Developmental Disabilities, 2024)
Autism spectrum disorder (ASD) is strongly associated with socio-cognitive impairments that may result in vulnerability to other mental health conditions, particularly anxiety disorders. This study examined the relationship between anxiety disorders and two key socio-cognitive impairments (cognitive empathy, affective empathy) in 60 adolescents (aged 11–18 years) with and without ASD. Adolescents with ASD showed cognitive empathy was negatively associated with separation anxiety disorder, whereas positive associations between affective empathy and generalized anxiety disorder, and positive marginal associations between affective empathy, social phobia, total anxiety, and separation anxiety disorder were observed. These findings suggest that cognitive and affective empathy show different patterns of associations with anxiety-related issues in ASD, and these differences should be considered for interventions and treatment programs.